2014
DOI: 10.14260/jemds/2014/2529
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Cyst in the Past and the Present

Abstract: BACKGROUND:Hydatid cyst is a parasitic infection that is widely endemic in India. It is a zoonotic disease with man being an accidental dead end host. Despite its world-wide affection, its diagnosis still remains a matter of challenge due to lack of an authentic gold standard for its early detection. In such cases, clinical judgment and high index of suspicion, in an endemic area is a worthy tool. AIMS AND OBJECTIVES: The study was undertaken to highlight important clinical features of hydatid cyst to help ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This study showed IAHC to be a fairly common condition. Though the disease is considered to be common in rural settings, our finding showed a relatively higher proportion of patients to be from the urban setting [ 15 ]. Bilutse et al from a different hospital in Addis Ababa also showed 60% of their patients with HC of the liver to be from urban settings [ 6 ].…”
Section: Discussionmentioning
confidence: 90%
“…This study showed IAHC to be a fairly common condition. Though the disease is considered to be common in rural settings, our finding showed a relatively higher proportion of patients to be from the urban setting [ 15 ]. Bilutse et al from a different hospital in Addis Ababa also showed 60% of their patients with HC of the liver to be from urban settings [ 6 ].…”
Section: Discussionmentioning
confidence: 90%
“…The life cycle of Echinococcus granulosus was first described by Haubner. [2][3][4] It is an important zoonotic and parasitic infection of humans, following ingestion of tapeworm eggs excreted in the faeces of infected dogs. 3 Echinococcosis is endemic in developing countries like South America, Middle East, Australia, India and Mediterranean countries where flocks of sheep and cattle are raised with dogs and hence more common in the rural population and with also the people involved in animal husbandry.…”
Section: Discussionmentioning
confidence: 99%
“…3 Echinococcosis is endemic in developing countries like South America, Middle East, Australia, India and Mediterranean countries where flocks of sheep and cattle are raised with dogs and hence more common in the rural population and with also the people involved in animal husbandry. 2,4,5 In India the highest prevalence is reported in Andhra Pradesh, Tamil Nadu, and Jammu and Kashmir…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations